PELATIHAN PENINGKATAN KEMANDIRIAN ANAK MELALUI KETERAMPILAN SELF-HELP - Bernike Juwita Permata Sari; Wahyu Priyono; Lena N. Pandjaitan (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Every child is expected to be able to develop according to the stages of their development, including aspects of social maturity. In the age range of 3-6 years at preschool age, children need stimulation to develop themselves from various kinds of social skills to be able to develop optimally. This research was conducted on Kindergarten A and Kindergarten B students by conducting observations and interviews at the assessment stage and the training process at the intervention stage. This study aims to increase understanding (knowledge) about independence, improve skills (skills) and improve attitude (attitude) in performing general self-help tasks (washing hands, making the bed) and self-help eating (preparing food and eating using spoons and forks ). The results of the training are quite effective, each class level there is only 1 training material that is not effective. Internal factors are the physical maturity of the child, while externally the environment, parenting, and the occupational status of the mother.